Digital Poverty In The Endemic Era: A Case Study Of The Bajau-Sama Community In Sabah Of East Malaysia (Journal of Namibian Studies : History Politics Culture, 2023)
Digitalisation has become a part of normal life reality and the Covid-19 pandemic has further accelerated the significance of digital world within the global community. This phenomenon has triggered digital poverty especially in Sabah in relation to issues such as accessibility, internet and gadgets. Understanding the importance of digital world especially during the endemic era, this study was initiated to perceive the extent of digital poverty phenomenon as how it was experienced and impacted the life of the Bajau community in Tuaran, specifically in these villages: Bolong Lama, Bolong Baru, Dempelang, Kota, Tembalang, Laya-laya and Lok Batik. A combination of both questionnaires and observation were utilised to obtain quantitative and qualitative data. In addition, theoretical and conceptual approaches related to digital poverty were applied. This study identified that the level of digital poverty among the Bajau community in the locations under study was digitally poor. Several factors such as personal, education, economy, physical, social and administration were recognised as the contributing factors to digital poverty issues, however, the administration/social factor was discovered as the main contributing factor. Digital poverty appears to influence the socioeconomic and community’s psychology due to lack of attention given by responsible parties. It is hoped that this paperwork has significantly contributed to academicians focussing on related knowledge epistemology as well as for the Bajau community to experience the nation development and not marginalised in digitalisation ecosystem in line with the Shared Prosperity Vision 2030 and Industrial Revolution 4.0 (IR4.0).